Analisis Penggunaan Sistem Face Recognition dalam Mengelola Absensi Karyawan di PT Bintang Inspeksi Indonesia - Arfiansyah Putra; Umar Mansyuri; Gagah Dwiki Putra Aryono (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The attendance system is one of the important components in human resource management in the company. Along with the development of technology, conventional attendance methods began to be replaced with more modern systems such as face recognition. This research aims to analyze the use of face recognition system in managing attendance at PT Bintang Inspeksi Indonesia. The method used in this research is descriptive qualitative, with a case study approach based on direct experience during Practical Work Lecture (KKP) activities. Data was collected through observation, interviews, and documentation. The results showed that the implementation of the face recognition system increased the efficiency of recording attendance, reduced the potential for data manipulation, and accelerated the process of recapitulating employee attendance. Despite challenges such as dependence on network quality and hardware, the system is considered effective and feasible to implement across the board. This study recommends improving the network infrastructure and training all employees on the use of the system.